PLANTING MODEL OF MAIZE (Zea mays L.) AND PLANTING TIME OF MUSTARD (Brassica juncea L.) IN INTERCROPING SYSTEMS ON GROWTH AND SEED YIELD OF MAIZE - Aini, Nurul; Guritno, Bambang; Cahyaningtyas, Rifa; Sugharto, Arifin Noor (PLANTROPICA: Journal of Agricultural Science, 2016)
The aim of the experiment was to investigate and evaluate planting model of maize and planting time of mustard in intercropping sistem on leaves area, total dry matter and seed yield of maize. The experiment design was at split plot, with 2 planting model (single and doble row) of maize and planting time of mustard (10 days prior to maize planting, along with maize planting, and 10 days after maize planting). The results showed that planting model of maize is not effected by time planting of mustard in intercropping systems. Double row planting of maize showed the leaves area, total dry matter and seed yield of maize were not significantly different from model of single row. Likewise mustard planting time showed no significant differnce among the three planting time on of the leaves area, total dry matter and seed yield of maize. The study indicate that the insertion of mustard plant on maize crops can improve land use. Land equivalent ratio in maize intercropping with mustard at 1.81.Key word : Planting model, planting time, intercropping, maize, mustard